Answer:
write your question properly...
Let's solve your equation step-by-step.<span><span><span><span><span>− 14 </span>+ <span>6x </span></span>+ 7</span> −<span> 2x </span></span>=<span> 1 + <span>5x</span></span></span>
Step 1: Simplify both sides of the equation.<span><span><span><span><span>−14 </span>+ <span>6x </span></span>+ 7 </span>− <span>2x </span></span>=<span> 1 +<span> 5x</span></span></span><span>
Simplify: </span><span><span><span>4x - </span><span>7 </span></span>= <span><span>5x</span> + 1</span></span><span><span><span>4x</span> − 7</span>= <span><span>5x </span>+ 1</span></span>
Step 2: Subtract 5x from both sides.<span><span><span><span>4x</span> − 7</span> − <span>5x </span></span>= <span><span><span>5x </span>+ 1</span> −<span> 5x</span></span></span><span><span><span>− x </span>− 7 </span>=1 </span>
Step 3: Add 7 to both sides.<span><span><span><span>−x </span>− 7</span> + 7</span>=<span> 1+7</span></span><span><span>−x</span>=8</span>
Step 4: Divide both sides by -1.<span><span><span><span><span>−x/</span><span>−1 </span></span></span></span>=<span><span><span> 8/<span>−1</span></span></span></span></span><span>x=<span> −8</span></span>
Answer:<span>x= <span>−<span>8
hope this helps :)</span></span></span>
Answer:
The roots are;
x = (2 + i)/5 or (2-i)/5
where the term i is the complex number representing the square root of -1
Step-by-step explanation:
Here, we want to use the completing the square method to solve the quadratic equation;
f(x) = -5x^2 + 4x -1
Set the function to zero
0 = -5x^2 + 4x - 1
So;
-5x^2 + 4x = 1
divide through by the coefficient of x which is -5
x^2 - 4/5x = -1/5
We now take half of the coefficient of x and square it
= -2/5^2 = 4/25
add it to both sides
x^2 - 4x/5 + 4/25= -1/5 + 4/25
(x- 2/5)^2 = -1/5 + 4/25
(x - 2/5)^2 = -1/25
Take the square root of both sides
x - 2/5 = √( -1/25
x - 2/5 = +i/5 or -i/5
x = 2/5 + i/5 or 2/5 - i/5
Answer:
1.33
Step-by-step explanation:
Answer:
96
Step-by-step explanation:
Multiply both sides of the equation by 8
move the constant to the right
calculate
divide both sides
solution